Preservation of Azotobacter chroococcum vegetative cells in dry polymers - Rojas-Tapias, Daniel; Corporación Colombiana de Investigación Agropecuaria - Corpoica (Pontificia Universidad Javeriana, 2014)
We studied the preservation of Azotobacter chroococcum C26 using three dry polymers: carrageenin, sodium alginate, and HPMC, using a method of accelerated degradation. Bacterial viability, as response variable, was measured at three temperatures in four different times, which was followed by calculation of bacterial degradation rates. Results showed that temperature, time of storage, and protective agent influenced both viability and degradation rates (P<0.05). We observed, using the Arrhenius thermodynamic model, that the use of polymers increased the activation energy of bacterial degradation compared to control. We obtained thermodynamic models for each polymer, based on the Arrhenius equation, which predicted the required time for thermal degradation of the cells at different temperatures. Analysis of the models showed that carrageenin was the best polymer to preserve A. chroococcum C26 since ~ 900 days are required at 4 ºC to reduce its viability in two log units. We conclude, therefore, that long-term preservation of A. chroococcum C26 using dry polymers is suitable under adequate preservation and storage conditions.